Analisis Fiqh Muamalah terhadap Penghasilan pada Aplikasi BuzzBreak - Aini, Fauqah Nuri; Handoko, Luqman Hakim; Armen, Rio Erismen (TAWAZUN: Journal of Sharia Economic Law, 2023)
The research aims to find out the mechanism for using the BuzzBreak application, and to analyze the process of earning income using the BuzzBreak application. The method used is descriptive qualitative and data sources were taken through library research. Where the research focuses on income (income) obtained by users of the BuzzBreak application. Based on the results of the study, the most probable Islamic contract is Ju’alah contract since there is an agreement from the application party to provide certain rewards to application users for achieving specified work results (natijah). This is also supported by the identification of the sale contract from the DSN fatwa No. 62 MUI/XII/2007 regarding the sale, as well as the opinion of the two high priests, namely the Syafi'i and Maliki schools of thought, who emphasize the point of selling at the point of uncertainty about the time it was made and about its success.